Organic 'islands' - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
With demand for organic foods nudging 40% in British supermarkets, the Sainsbury s chain launched plans early 2000 for partnerships with landowners in Grenada and St Lucia to start biological cultivation on around 300 ha initially. Easier said than...